Effect of task-shifting HIV testing from laboratory personnel to nurses on paediatric and adolescent HIV testing rate and yield in rural Nigeria: a prospective before-and-after study - Oriaku Ofem, MD; Tongdiyen Laura Jasper, MD; Nguavese Torbunde, MD; Murna Yashimankut, MD; Hussaini Sadiq, BSc; Rosemary Ejekam, MD; Daniel Ikeda, BA; Emmanuel Aiyenigba, MD; Bruce Agins, MD; Nadia Sam-Agudu, MD (Elsevier, 2019)
Background: Nigeria has the second highest burden of HIV in children younger than 15 years (220 000) and adolescents 10 -19 years (230 000) in the world. Unfortunately, fewer than a quarter of these children and adolescents are identified and given access to treatment. Decentralisation of HIV testing services to high-yield service delivery points can facilitate identification of undiagnosed HIV-positive children and adolescents. However, decentralisation of testing services is still uncommon, partly due to existing health-care professional boundaries. We evaluated the effectiveness of task-shifting HIV testing services from specialised laboratory personnel to nurses to improve HIV case identification in paediatric and adolescent clients. Methods: We established a testing point for patients aged 0-19 years in the inpatient ward at a secondary health-care facility in a rural district with high prevalence of HIV in north-central Nigeria. Paediatric nurses were trained by laboratory personnel to provide HIV testing to children and adolescents admitted to the ward. We reviewed the hospital ward admission records and laboratory HIV testing records for patients aged 0-19 years to establish a pre-intervention baseline. Findings: In the 3 months before the intervention when HIV testing services were provided only by laboratory personnel, 276 children and adolescents were admitted (mean 92·0 admissions/month), of whom only 22 patients (8%) underwent HIV testing and no positive cases were identified. However, in the 4-month intervention period between April and July, 2018, 179 paediatric or adolescent clients were admitted (44·8 admissions/month), of whom 169 (94%) were tested for HIV by nurses and four HIV-positive children were newly identified (a 2·4% yield). Linkage to care and antiretroviral therapy initiation was achieved for all newly identified children within 24 h of diagnosis. Interpretation: Task-shifting of paediatric and adolescent inpatient HIV-testing services to nurses was more effective in HIV case identification than was testing by laboratory personnel. In settings where limited human resources remains a major challenge, implementation and scale-up of task shifting for testing services can significantly improve HIV case identification and, therefore, treatment coverage in children and adolescents. Funding: CDC-PEPFAR.